Caracterização do perfil produtivo e contagem total de bactérias de leite de cabra em unidades de base familiar nos estados do Ceará e do Rio Grande do Norte. - Ramos, Marcela Oliveira (2012)
Grande do Norte and Ceará, to promote the sustainable development of dairy goat in semi-arid northeastern Brazil. Information related to socio-economic profile of producers and production systems used were obtained through personal interviews using a questionnaire applied to 19 properties in Rio Grande do Norte and Ceará 10 properties. The quality of milk was determined by Total Bacterial Count (TBC) in samples collected after the morning milking for a period of three days before and three days after the adoption of good practices recommended by the project milking “Kit Manual for Embrapa Milking Goats dairy “. In both states, the production systems in MPUs characterized by being so extensive and low technological application, limited water and forage resources in semi-arid. It was found that there are difficulties related to nutritional managements, reproductive health and milking procedures adopted, and the need to sensitize producers with information to promote goat rearing as well as ensure that the final product is inserted in the market with quality. In evaluating the quality of milk, the average TBC found were 5.2 x 105 UFC / mL and 4, 1 x 105 UFC / mL before and after the use of technological kit respectively, since the quality of milk produced after use kit technology within the parameters of hygiene and quality established by the legislation. It is concluded that the exploitation of dairy goats in northeastern states as a technical activity economically viable, provided that use appropriate technologies and to prioritize, especially food and health management.